Gratification Phenomena in Infancy: A Report of Twenty-Nine Children - Koul, Roshan; AlFutaisi, Amna; Mani, Renjith; Abdelrahim, Rana; AlAdi, Azza (Journal of Pediatric Neurology, 2020)
Twenty-nine children with gratification phenomena seen in last 10 years (January 2008 to December 2017) were analyzed retrospectively. A proper history, eyewitness account, and video recordings of the event helped in making the diagnosis. Twenty-seven out of 29 (93%) children with gratification phenomena were females. Four patterns of gratification phenomena were seen. Three of these patterns not described before are reported. A typical gratification phenomenon was seen in 16 of 29 (55%) children. At the time of referral, 24% of these children were labeled epileptic and were on antiepileptic medication. This benign condition has to be recognized and extensive investigations should be avoided.
Keywords: gratification phenomena; children; benign; epilepsy mimics; paroxysmal disorder